2016
DOI: 10.1016/j.fct.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic atrazine exposure alters zebrafish and human miRNAs associated with angiogenesis, cancer, and neurodevelopment

Abstract: MicroRNAs (miRNAs) are short, single-stranded RNA that regulate post-transcriptional control of mRNA translation. Knowledge on the role of these critical regulators in toxicological responses in increasing, but is still limited. Atrazine is a herbicide used throughout the Midwestern US that is reported to frequently contaminate potable water supplies above the maximum contaminant level of 3 parts per billion. Atrazine is a suspected endocrine disrupting chemical and studies have begun to investigate the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 81 publications
1
47
0
Order By: Relevance
“…4950 In a previous study, we also first began to investigate epigenetic mechanisms behind the observed alterations in larvae and adult zebrafish by evaluating changes in microRNA (miRNA) expression following the same atrazine exposure regimen (i.e., an embryonic atrazine exposure at 0.3, 3, or 30 ppb throughout embryogenesis, 1–72 hpf). 47 Results from that study revealed alterations in miRNAs that were associated with angiogenesis, cancer, and neurodevelopment, but there are still questions on additional epigenetic mechanisms of atrazine toxicity including DNA methylation. 47 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4950 In a previous study, we also first began to investigate epigenetic mechanisms behind the observed alterations in larvae and adult zebrafish by evaluating changes in microRNA (miRNA) expression following the same atrazine exposure regimen (i.e., an embryonic atrazine exposure at 0.3, 3, or 30 ppb throughout embryogenesis, 1–72 hpf). 47 Results from that study revealed alterations in miRNAs that were associated with angiogenesis, cancer, and neurodevelopment, but there are still questions on additional epigenetic mechanisms of atrazine toxicity including DNA methylation. 47 …”
Section: Introductionmentioning
confidence: 98%
“…20, 3943 However, understanding the epigenetic alterations contributing to atrazine toxicity is still under investigation. 4447 …”
Section: Introductionmentioning
confidence: 99%
“…A least significant difference (LSD) post hoc test was performed if significance was met for the ANOVA test to establish when sets of data were different from each other, similar to other studies in our laboratory (Peterson et al, 2010;Wirbisky et al, 2015;Wirbisky et al, 2016). expression (p = 0.3040; see Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the expression changes in tpd52l1 could impact how touch reflexes or blood circulation are affected at 36 hpf or impact the completion of morphogenesis for the 60 hpf alterations. In addition, from previous and ongoing studies, we know that atrazine also changes expression of other genes too and the interactions and relationships between the expression of tpd52l1 with these other gene targets needs further study (Weber et al, 2013;Wirbisky et al, 2015;Wirbisky et al, 2016). Overall, additional experiments need to be performed to better understand how exactly atrazine plays a mechanistic role in changing expression of the transcriptome and how these gene expression changes translate to adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation